The influence of parent sport behaviours on children's development: Youth coach and administrator perspectives - Ross, A. J.; Mallett, C. J.; Parkes, J. F.; Strachan, L. (International Journal of Sports Science and Coaching, 2015)
There has been much literature and anecdotal accounts reporting poor parental behaviours in the youth sporting context. Youth coaches and administrators, who regularly interact with parents within the youth sporting domain, are potentially a key source for investigating the influence of parents` sport-related behaviours on youths` sporting experiences. Nevertheless, the voice of coaches and administrators has been limited. In this study, the authors sought to develop an understanding of youth sport coaches` and administrators` perspectives of parent sport behaviours` influence on children`s development across various sport settings. Additionally, the authors explored participant awareness of and their perspectives of efficacy in relation to current parent education programs in Australia. Semi-structured interviews were conducted with twelve youth sport coaches and administrators (eight coaches, four administrators; eight males, four females) with an average of nine years experience. Coaches and administrators reported considerably more frequent negative interactions with parents than positive interactions. Participants also reported more negative observations of parent-child communications than positive observations. Four participants reported exposure to parent education efforts but all perceived these approaches to be inadequate. Recommendations, practical implications, and future avenues of research are discussed.